The Influence of the Work Environment, Motivation and Human Resources Competency on Employee Performance at the Education, Culture, Youth and Sports Office of Gorontalo Province - Hien Ishak; Ellys Rachman; Amrain Mustafa (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research aims to: 1) find out how the influence of the Work Environment partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 2) find out how the influence of the motivation partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 3) find out how the influence of the human resources competency partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 4) how the Work Environment, Motivation, and Human Resources Competence Simultaneously on Employee Performance in the Education, Culture, Youth and Sports Office of Gorontalo Province. This research uses an explanatory research method; the quantitative method emphasizes objective phenomena and maximizes objectivity. This research design uses numbers, statistics, structure, and controlled experiments, with data collection techniques through observation, interviews, and documentation. A sample of 141 people from a total population of 218 people including the Head of the Education, Culture, Youth and Sports office of Gorontalo Province. The results showed that: 1) partially, the work environment does not have a positive influence on employee performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 2) partially motivation has a positive and simultaneous influence on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 3) partially human resources competencies have a positive and simultaneous influence on employee performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 4) simultaneously, the variables of the Work Environment, Motivation, and Competence of Human Resources have a positive effect on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province.